Karakteristik Pati Kacang Tunggak (Vigna unguiculata) dan Sohunnya - Chatarina Lilis Suryani; Dwi Purwantana; Haryadi Haryadi (agriTECH, 2001)
Starch was extracted from cowpea (Vigna unguiculata) and characterized for solubility, swelling power and amylographic properties. The starch was then use to make starch noodle which then was characterized for texture, tensile strength, swelling volume and cooking loss. Arenga (Arenga pinnata) starch and its noodle were also characterized for comparison. Cowpea starch contained higher amylose then arenga starch did. The Brabender amylographic patterns of the cowpea starch gave no pasting peak, higher stability of pastes, higher viscosity of the gels and higher total retrogradation of the gel. Cowpea starch could be used to substitute arenga starch in starch noodle making at the propostion of 20, 40, 60, 80, and 100%. These results indicated that subtitution of 20-100% gave a better noodle quality, compared to that of arenga starch.